Recurrent Clostridium difficile infection: From colonization to cure. (August 2015) - Shields, Kelsey; Araujo-Castillo, Roger V.; Theethira, Thimmaiah G.; Alonso, Carolyn D.; Kelly, Ciaran P.
Abstract: Clostridium difficile infection (CDI) is increasingly prevalent, dangerous and challenging to prevent and manage. Despite intense national and international attention the incidence of primary and of recurrent CDI (PCDI and RCDI, respectively) have risen rapidly throughout the past decade. Of major concern is the increase in cases of RCDI resulting in substantial morbidity, morality and economic burden. RCDI management remains challenging as there is no uniformly effective therapy, no firm consensus on optimal treatment, and reliable data regarding RCDI-specific treatment options is scant. Novel therapeutic strategies are critically needed to rapidly, accurately, and effectively identify and treat patients with, or at-risk for, RCDI. In this review we consider the factors implicated in the epidemiology, pathogenesis and clinical presentation of RCDI, evaluate current management options for RCDI and explore novel and emerging therapies. Highlights: Recurrent CDI (RCDI) is a common complication following ∼25% of initial CDI cases. RCDI is challenging: there is no uniformly effective therapy and few reliable data. We evaluate current and novel RCDI treatments and propose treatment approaches. New evidence favors vancomycin and fidaxomicin over metronidazole for RCDI therapy. FMT has emerged as a leading choice for treatment of multiply recurrent CDI.